Increasing entrepreneurship and local food security through optimising taro based on an integrative agribusiness system - Alda Deria,; Rendi Prayoga,; Aufa Rafiqi,; Amanda Elza Pratiwi,; Muhammad Zikri,; Siska Alicia Farma, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Mentawai is an area where the majority of the population works as fishermen and farmers. The superiority of the agricultural sector in Mentawai is supported by the soil conditions that are fertile enough to be planted with various types of plants. One of the crops is the taro plant, which the Mentawai people utilise as a staple food. People tend to prioritise imported rice in Mentawai because local rice production is insufficient to meet basic needs. The scarcity of staple food becomes apparent when the ship that transports goods to Mentawai docks only once a week. To address these issues, a program was developed to empower Dasawisma women, who act as cadres for family entrepreneurship and local food security, through training and mentoring activities. This program focuses on optimising taro through an integrative agribusiness system. The participatory observation method used involves students going directly to the field and participating in the implementation of the program, which includes training, mentoring, and collaboration with taro farmers. The program provides support for product processing and marketing diversification. Additionally, the community gains knowledge and skills in processing taro into various products such as taro chips, flakes, jam, cakes, and flour.